Prevalence of depression symptoms and its influencing factors among pregnant women in late pregnancy in urban areas of Hengyang City, Hunan Province, China: a cross-sectional study. Issue 9 (1st September 2020) - Yu, Yunhan; Zhu, Xidi; Xu, Huilan; Hu, Zhao; Zhou, Wensu; Zheng, Baohua; Yin, Shilin
Abstract : Objectives: To evaluate the prevalence of depressive symptoms and its influencing factors in late pregnancy. Design: Cross-sectional study. Setting: Fourteen community in urban areas of Hengyang City. Participants: The study conducted from July to October 2019, and surveyed 813 women in late pregnancy who lived in urban areas of Hengyang for more than 6 months, signed an informed consent and were without cognitive disorders, severe mental illnesses or other serious diseases. Measures: Perinatal depression symptoms were evaluated using the Patient Health Questionnaire-9, and perinatal anxiety symptoms were evaluated using the Generalised Anxiety Disorder-7 Scale. Sociodemographic variables, obstetric characteristics, lifestyle behaviours, family factors, social support, sleep quality and self-efficacy were obtained through structured questionnaires. Results: The prevalence of depression symptoms among pregnant women in late pregnancy was 9.2% (95% CI 7.2%–11.2%). Protective factor: age between 25 and 29 years (OR=0.398; 95% CI 0.16–0.991). Risk factors: a normal relationship with her mother-in-law (OR=5.309; 95% CI 1.122–4.184), artificial insemination (OR=4.339; 95% CI 1.492–12.623), no exercise during pregnancy (OR=2.666; 95% CI 1.177–6.039), low self-efficacy (OR=4.253; 95% CI 1.518–11.916), low social support (OR=2.371; 95% CI 1.206–4.661), poor sleep quality (OR=2.134; 95% CI 1.131–4.027), existence of anxiety symptoms (OR=17.654; 95% CI 8.494–36.689). Conclusion: The prevalence of depression symptoms is lower than that in developing countries, but due to the large population base of China, the problem should still be taken seriously. To prevent mental disorders of pregnant women, early screening for mental disorders, promotion of healthy lifestyles, mental healthcare during pregnancy and improved family and social support should be implemented during pregnancy nursing.